2014
DOI: 10.1111/jsm.12461
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Premature Ejaculation, Lower Urinary Tract Symptoms, and Erectile Dysfunction in Middle-Aged Korean Policemen

Abstract: Introduction There is controversy concerning the relationship between premature ejaculation (PE) and erectile dysfunction (ED), as well as the scan data regarding the association between PE and lower urinary tract symptoms (LUTS). Aims We performed this study to evaluate the association between PE and ED or LUTS. Methods A total of 2,591 policemen aged 40–59 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 28 publications
1
16
2
Order By: Relevance
“…Several theories have tried to elucidate the associations between ED and PE, for example, a M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 9 compensatory mechanism for the inability to maintain the erection, reduction of nitric oxide (NO), and NO synthase and autonomic hyperactivity theory [22][23] . In addition, metabolic syndrome and testosterone may play an important role in ED and PE 6,24 . Convincing evidence show that PDE-5 inhibitors provide meaningful treatment benefit in a population of men with PE and comorbid ED 19 .However, a potential role for PDE-5 inhibitors in the treatment of PE without ED is controversial.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several theories have tried to elucidate the associations between ED and PE, for example, a M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 9 compensatory mechanism for the inability to maintain the erection, reduction of nitric oxide (NO), and NO synthase and autonomic hyperactivity theory [22][23] . In addition, metabolic syndrome and testosterone may play an important role in ED and PE 6,24 . Convincing evidence show that PDE-5 inhibitors provide meaningful treatment benefit in a population of men with PE and comorbid ED 19 .However, a potential role for PDE-5 inhibitors in the treatment of PE without ED is controversial.…”
Section: Discussionmentioning
confidence: 97%
“…However, many patients, might not respond adequately to SSRIs, particularly those with erectile dysfunction(ED), likely because PE and ED are associated with each other 4,6 .Several recent studies have investigated the role of phosphodiesterase type 5(PDE-5) inhibitors, which are the first-line treatment for ED, reporting efficacy in the treatment of PE in the absence ofED [7][8] . It is noteworthy that PDE-5 inhibitors do not pharmacokinetically interact with SSRIs, and the combination of both is well tolerated 9 .In addition, efficacy and safety regarding the combination of PDE-5 inhibitors and SSRIs versus PDE-5 inhibitors or SSRIs monotherapy have also been investigated in the past decade [10][11][12][13] .…”
mentioning
confidence: 99%
“…Besides the improvement of LUTS, tamsulosin can help the subjective symptoms of PE in patients with LUTS + PE (Choi et al, 2014). In recent clinical trial, LUTS and ED were significantly and independently correlated with PE (Lee, 2014). Retrograde or abnormal ejaculation was the most commonly reported side effect in the patients treated with silodosin (Cho & Yoo, 2014).…”
Section: Prostate and Prostatic Diseases In The Pementioning
confidence: 98%
“…Recently Lee et al reported that PE in Korean policemen is associated with ED and lower urinary tract symptoms (LUTS) including prostatic disease, which might be the important disease background for the PE (41). Alpha-1 adrenoceptor antagonist (alpha-1 blocker) is widely accepted as the first-line treatment for LUTS caused by benign prostatic hyperplasia.…”
Section: Alpha-1 Adrenoceptor Antagonist (Alpha-1 Blocker)mentioning
confidence: 99%